Analysis of Shallow Groundwater Quality in Joho Village, Mojolaban, Sukoharjo - Hashfi Hawali Abdul Matin; Siti Rachmawati; Lia Kusumaningrum; Iva Yenis Septiariva; Purwono Purwono (Universitas Diponegoro, 2020)
Water is the main need for humans, so the quality and quantity must be maintained. The purpose of this research is to analyze the problems in Joho Village in the form of cloudy water so that the community feels disturbed. In this study, the water quality test was carried out using the Indonesian National Standard and with a random sampling technique. Samples were taken from 3 points in residents' houses and 2 points in public facilities, namely in parks and places of worship. Data analysis was carried out by descriptive quantitative. There is one sample that does not meet the quality standard for odor parameters, namely at the observation point in the park. However, for the turbidity parameter, all samples showed that none met the quality standards, namely 116, 48, 100, 136, 130 NTU. The solution that can be done by residents of Joho Village is to do pavement and closure in the area around the shallow well and perform simple filtration consisting of Zeolite (10 - 30 mm), Zeolite (5 - 10 mm), Silica sand (4 - 30 mesh), Activated Carbon, and Sponge.